Entrepreneurship and global competitiveness in regional economies determinants and policy implications - Libecap, Gary D.; Hoskinson, Sherry (Advances in the study of entrepreneurship, innovation, and economic growth ;, 2011)
This volume, comprised of authors from the U.S., Canada, Africa, and Europe, centers on the development, transformation, and role of geographic /regional economies-- specifically in the globalized, post-2009 era. The authors address topics that every region must consider in responding to idea age, globally competitive, regionally driven economies. The volume builds on a large body of scholarship specific to regional economic development and geography by providing a much needed post-2009 perspective on regional economic environments and activities. Among the topics addressed are the emergence and boundaries of new economic geographies; the actors, characteristics, and functions of regional innovation systems as well as the opportunities and challenges associated with region-specific cultural and environmental interactions. It also examines the relationship of regional economies to diminishing country based economies and the critical relationship to globalization.